Plague, Pentecostalism, and Pastoral Guidance: Luther’s Wisdom for the Contemporary Church - Butler, Geoffrey (Pneuma, 2021)
Abstract Plagues and pandemics are nothing new for the Christian church. Throughout its history, believers have been forced to grapple with outbreaks, the latest being the COVID -19 crisis of 2020. As a relatively young branch of the Christian faith, Pentecostalism itself does not have a great deal of experience with this subject compared to many older traditions. In addition, with its emphasis on divine healing, a triumphalist attitude has unfortunately hindered some segments of the movement from developing a robust response to sickness and suffering at all. Martin Luther’s sixteenth-century response to the Black Death outbreak in Germany, however, might offer a prime example for contemporary Pentecostals to emulate. His pastoral wisdom, approach to suffering, and distinctive theology of the cross together compose a prudent yet ultimately optimistic take on how Christians should behave in such instances, making his voice an invaluable one for the contemporary church to learn from.